PENGARUH LITERASI KEUANGAN, SIKAP KEUANGAN DAN PENGGUNAAN FINANCIAL TECHNOLOGY TERHADAP KEPUTUSAN INVESTASI MELALUI PERILAKU KEUANGAN SEBAGAI VARIABEL MODERATING PADA SISWA SMA NEGERI 1 SITUBONDO - Danial, Muhammad; Fandiyanto, Randika; Ariyantiningsih, Febri (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The aim of this research is to analyze the influence of variablesThe Influence of Financial Literacy, Financial Attitudes and Use of Financial Technology on Investment Decisions through Financial Behavior as a Moderating Variable in Situbondo 1 Public High School Students. By using the Partial Least Square (PLS) Structural equation model. Results of direct influence hypothesis testing using the Smart PLS 3.0 application. Financial literacy has a negative but significant effect on investment decisions, Financial attitude has a negative but not significant effect on investment decisions, Use of Financial Technology has a positive but not significant effect on investment decisions, Financial behavior is significantly moderating variable for the influence of financial literacy on investment decisions, financial behavior is significantly the moderating variable for the influence of financial attitudes on investment decisions, and financial behavior is significantly the moderating variable for the influence of the use of financial technology on investment decisions.